30 Years of ForumAlpinum: Contributions of ISCAR to International Research Cooperation and Sustainable Development in the Alps and Beyond - Thomas Scheurer; Elisa Frank; Valerie Braun; Irma Potočnik Slavič; Janez Nared; Živa Novljan (Mountain Research and Development)
The Forum Landscape, Alps, Parks (FoLAP) at the Swiss Academy of Sciences, supported by the Swiss Academy of Humanities and Social Sciences, hosts the office of the International Scientific Committee on Research in the Alps (ISCAR). On the occasion of the 30th anniversary of ForumAlpinum, FoLAP invited ISCAR to present the history and impact of this Alpine-wide conference, organized by ISCAR in collaboration with national partners. Thirty years after the first ForumAlpinum in 1994, we trace its evolution in terms of interaction with the scientific and political environment. We highlight some success factors and challenges throughout the 14 editions of this interdisciplinary conference, which aims to link natural sciences, humanities, and society for sustainable development in the Alps, according to the principles of the Alpine Convention.